The value of a vaginal sample for detecting PAMG-1 (Partosure®) in women with a threatened preterm delivery (the MAPOSURE Study): protocol for a multicenter prospective study - Emilie Marie; Guillaume Ducarme; Marion Boivin; Virginie Badon; Hélène Pelerin; Aurélie Le Thuaut; Zeineb Lamoureux; Valéry-Pierre Riche; Norbert Winer; Thibault Thubert; Vincent Dochez (BMC, 2020)
Abstract Background Threatened preterm delivery (TPD) is the leading cause of inpatient admissions during pregnancy. The ability to predict the risk of imminent preterm delivery is thus a major priority in obstetrics. The aim of our study is to assess the diagnostic performance of the test to detect the placental alpha microglobulin 1 (PAMG-1) for the prediction of delivery within 7 days in women with TPD. Methods This is a prospective multicenter diagnostic study. Inclusion criteria are singleton pregnancy, gestational age between 24 + 0 and 33 + 6 weeks inclusive, cervical measurement 25 mm or less assessed by transvaginal ultrasound (with or without uterine contractions), clinically intact membranes and cervical dilatation < 3 cm assessed by digital examination. According to the current protocol, when a women presents with TPD and the diagnosis is confirmed by transvaginal ultrasound, a vaginal sample to test for genital infection is performed. At the same time, the midwife will perform the PartoSure® test. To perform this analysis, a sample of cervicovaginal secretions is taken with the vaginal swab furnished in the test kit. The primary outcome is the specificity of the PartoSure® test of women who gave birth more than 7 days after their hospitalization for TPD. The secondary outcomes are the sensitivity, PPV, and NPV of the Partosure® test and the factors associated with false positives (with a univariate logistic regression model). Starting with the hypothesis of an anticipated specificity of 89%, if we want to estimate this specificity with a confidence interval of ± 5%, we will require 151 women who do not give birth within 7 days. We therefore decided to include 400 women over a period of two years to have a larger number of events (deliveries within 7 days). Discussion The different tests already used such as fetal fibronectin and phIGFBP-1, are not sufficiently relevant to recommend their use in daily practice. The different studies of PAMG-1 described above thus provide support for the use of this substance, tested by PartoSure®. Nonetheless, other larger studies are necessary to validate its use in daily practice and our study could answer this question. Trial registration NCT03401255 (January 15, 2018)